2019
DOI: 10.1007/s13671-019-00265-2
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Treatment Approaches for Cutaneous Field Cancerization

Abstract: Purpose of Review Field cancerization describes the phenomenon that multiple heterogenous mutations may arise in an area exposed to chronic carcinogenic stimuli. Advances in the understanding of cutaneous field cancerization have led to novel therapeutic approaches to the management of actinic keratoses (AKs). Herein, we review the literature on the pathophysiology and emerging research of field cancerization in dermatology. Recent Findings The classification systems for grading AK lesions are being refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 89 publications
2
12
0
Order By: Relevance
“…Interestingly, the slight expression of vimentin, detectable also in perilesional controls ( Figure 2 A), but not in unrelated epidermal samples from healthy skin (data not shown), suggested a possible beginning of subversion of the epithelial/mesenchymal marker expression in the area adjacent to AK lesions. These observations are consistent with the widely proposed concept of “cancerization field” [ 25 ]. It is well known that changes in phenotypic features during EMT are the results of a complex gene reprogramming driven by different transcription factors.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the slight expression of vimentin, detectable also in perilesional controls ( Figure 2 A), but not in unrelated epidermal samples from healthy skin (data not shown), suggested a possible beginning of subversion of the epithelial/mesenchymal marker expression in the area adjacent to AK lesions. These observations are consistent with the widely proposed concept of “cancerization field” [ 25 ]. It is well known that changes in phenotypic features during EMT are the results of a complex gene reprogramming driven by different transcription factors.…”
Section: Resultssupporting
confidence: 92%
“…These results suggested that the FGFR2c/FGFR3c/FGFR4/Snail1 expression profile could be indicative of KIN I lesions with a malignant tendency. Moreover, as previously observed for vimentin, the mesenchymal FGFR2c isoform, as well as FGFR4, which are not normally expressed in keratinocytes [ 14 ], appeared detectable also in perilesional controls ( Figure 3 B,D), suggesting a possible initiation of FGF/FGFR axis subversion in the area adjacent to AK lesions compatible with the establishment of a “cancerization field” [ 25 ]. The analysis of data from all KIN I sample compared their perilesional controls, confirmed the opposite trend of FGFR2b and FGFR2c genes ( Figure 3 E), as well as the induction of FGFR4 ( Figure 3 E), which became significant when the entire cohort of AK lesions were statistically analyzed by Wilcoxon test ( Figure 3 F).…”
Section: Resultssupporting
confidence: 75%
“…Several simultaneous cSCC or a single invasive cSCC surrounded by various actin keratoses can develop in a single area of the body, the called field of cancerization ( 68 ).…”
Section: Tumor Resectionmentioning
confidence: 99%
“…Actinic keratosis (AK) is reported by some authors as a precancerous lesion [2]; some others consider AK as an incipient form of squamous cell carcinoma (SCC) [6]. If referring to the histologically abnormal epithelium adjacent to tumor tissue, AKs can be also referred to as ''field of cancerization,'' and this underlies the transformation of photodamaged skin into AKs and potentially cutaneous SCC [7,8].…”
Section: Introductionmentioning
confidence: 99%